The Impact of Maxillary Expansion on Adults' Nasal Breathing: A Systematic Review and Meta-Analysis. Issue 6 (November 2021) - Calvo-Henriquez, Christian; Megias-Barrera, Joaquim; Chiesa-Estomba, Carlos; Lechien, Jerome R.; Maldonado Alvarado, Byron; Ibrahim, Badr; Suarez-Quintanilla, David; Kahn, Sandra; Capasso, Robson
Objective: Nasal surgery fails to restore nasal breathing in some cases. Maxillary constriction is suggested as a major cause of failure. It is thought that maxillary constriction leads to the closure of the internal and external nasal valves. Moreover, it is well established in the literature that maxillary expansion, both in adults and children, increases upper airway volume. However, it is yet unclear whether maxillary expansion may improve nasal function. Review Methods: Pubmed (Medline), the Cochrane Library, EMBASE and Trip Database were checked by two authors from the Rhinology Study Group of the Young Otolaryngologists section of the International Federation of Otorhinolaryngological Societies. Two authors extracted the data. The main outcome was expressed as the value (in variable units) prior to treatment (T0), after expansion procedures (T1), after the retention period (T2), and after a follow-up period (T3). Results: A total of 10 studies (257 patients) met the inclusion criteria. The data pooled in the meta-analysis reveals a statistically significant reduction of 0.27 Pa/cm 3 /s (CI 95% 0.15, 0.39) in nasal resistance after palatal expansion As far as subjective changes are concerned, the pooled data for the change in the NOSE score shows a statistically significant mean reduction after maxillary expansion of 40.08 points (CI 95% 36.28, 43.89). Conclusion: The initial available evidence is too limited to suggest maxillary expansion as a primary treatment option to target nasal breathing. However the data is encouraging with regards to the effect of maxillary expansion on nasal function. Further higher quality studies are needed in order to define clearer patient selection criteria, distinguish optimal techniques, and demonstrate long-term efficacy in long term follow up studies.